A new lean no time test baking method with improved discriminating power. (March 2017) - Dupuis, Brigitte; Fu, Bin Xiao
Abstract: In response to customer concerns related to gluten strength in commercial baking, the Canadian Grain Commission assessed whether the Canadian Short Process (CSP) test bake method was generating useful data related to intrinsic strength of wheat varieties. Assessment of CSP loaf volume data for Canadian variety trials spanning 2003 to 2013 showed very little correlation with dough strength parameters as measured by farinograph and extensigraph. A lean no time (LNT) test baking method was developed that can better discriminate genotypes and provide objective indicators of the effect of intrinsic dough strength on baking quality. From early method development, through method validation and verification using diverse sets of samples targeting different Canadian wheat classes and grown in three different crop years, results showed the LNT method to be more discriminating and easily adopted by other laboratories. In 2015, the LNT method was adopted as the method of choice in future Canadian variety registration trials. The LNT method is fast, simple and well-suited to high throughput test baking conditions encountered in the evaluation of large numbers of breeder lines. A new objective parameter, loaf top ratio, was also introduced and found to correlate well with dough strength and dough handling properties. Highlights: A lean no time test baking method was developed. The method is fast and simple and well-suited to high throughput conditions. A new objective parameter, loaf top ratio, was introduced. Strong correlations were found between loaf parameters and dough strength. The lean no time test baking method can be widely adopted.